2016
DOI: 10.5114/fn.2016.62534
|View full text |Cite
|
Sign up to set email alerts
|

Effect of recombinant Lactococcus lactis producing myelin peptides on neuroimmunological changes in rats with experimental allergic encephalomyelitis

Abstract: A b s t r a c t

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…It serves as a starter culture for the production of a variety of cheeses, as well as other dairy products such as sour cream and buttermilk. Owing to the long history of safe consumption and the availability of molecular tools, lactococci have a great potential as mucosal delivery vehicles for therapeutic and prophylactic molecules (Bermudez-Humaran et al 2011 ; Hugentobler et al 2012 ; del Carmen et al 2013 ; Szatraj et al 2014 ; Kasarełło et al 2016 ). The ability of L. lactis to adhere to the intestinal mucosa can potentially prolong the contact with the host, and therefore favour its persistence in the gut.…”
Section: Introductionmentioning
confidence: 99%
“…It serves as a starter culture for the production of a variety of cheeses, as well as other dairy products such as sour cream and buttermilk. Owing to the long history of safe consumption and the availability of molecular tools, lactococci have a great potential as mucosal delivery vehicles for therapeutic and prophylactic molecules (Bermudez-Humaran et al 2011 ; Hugentobler et al 2012 ; del Carmen et al 2013 ; Szatraj et al 2014 ; Kasarełło et al 2016 ). The ability of L. lactis to adhere to the intestinal mucosa can potentially prolong the contact with the host, and therefore favour its persistence in the gut.…”
Section: Introductionmentioning
confidence: 99%
“…But, there are some advantages in applying EPs compared to pure therapeutic proteins. Regarding inevitable hydrolysis of therapeutic proteins after oral administration, the reported results have been dose-dependent (Kasarełło et al, 2015(Kasarełło et al, , 2016. On the other hand, the purification of proteins is the most expensive step in the production of recombinant proteins.…”
Section: Discussionmentioning
confidence: 99%
“…These findings indicated that OT induction is not related to the host viability. Kasarełło et al (2015, 2016) manipulated LL to express secretory forms of MOG35‐55, MBP85‐97, and PLP139‐151. The authors revealed that oral gavage of the EP lysate improves clinical signs of EAE only in high dose; while, treatment with low dosages had no significant effects on EAE features.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…jensenii 1153–1666 Reduction in transmission of a chimeric simian/HIV 3 after repeated vaginal tests in macaques Lagenaur et al, 2011 Dendritic cell-targeting peptide fused with PEDV 4 core neutralizing epitope antigen Lb. casei ATCC 393 Antiviral probiotic vaccine against PEDV 4 in pigs Wang et al, 2017 Anti-inflammatory Pentadecapeptide BPC-157 L. lactis NZ9000 Decrease ROS 5 concentration in fibroblast cells as possible treatment against IBD 6 and GIT 7 inflammations Škrlec et al, 2018 EDG 8 , TFF 9 L. lactis PSM565 Repair of mucosal epithelial barriers, accelerate cells migration Huynh & Li, 2015 Cathelicidin L. lactis NZ3900 Reduction of inflammation in mice with colitis Zhang et al, 2016b , Wong et al, 2017 α-melanocyte-stimulating hormone B. longum HB15 Anti-inflammatory effect during ulcerative colitis induction in rats Wei et al, 2016 Anticancer Kisspeptin L. lactis NZ9000 Inhibition of HT-29 proliferation and migration, mediating apoptosis, down-regulation MMP-9 10 expression Zhang et al, 2016a TFF 11 L. lactis (sAGX0085) Reduction of days with ulcerative oral mucositis in locally advanced head and neck cancer patients Limaye et al, 2013 Immune stimulation Myelin peptide fragments L. lactis IBB360 Decrease of histopathological changes, reduction of serum IL-1b, IL-10 and TNF-α Kasarello et al, 2016 Gliadin L. lactis MG1363 Suppression of local and systemic gluten-sensitive disorders in non-obese diabetic mice Huibregtse et al, 2009 1 ...…”
Section: Bioactive Peptides From Genetically Engineered Probiotics An...mentioning
confidence: 99%